(untitled) (UKLO Proceedings, 2025)
The separation of critical infrastructure as a security and operational term is a relatively new phenomenon. However, although the term "critical infrastructure" is relatively new in the international community, this does not mean that its de facto existence has not been previously regulated or treated in an international context. The Geneva Conventions do not recognize critical infrastructure as such. However, this does not mean that legal protection is absent. Partly through norms directly addressing de facto critical infrastructure, and partly through the method of analogy, critical infrastructure in the ius in bello context is subject to protection on multiple grounds. series of provisions of treaty law and customary law protect civilian objects of essential importance, in areas where there is an active armed conflict or de facto occupation. However, the factual situation is difficult to reconcile with the legal one. However, it is not impossible. Through the method of analogy and legal interpretation, the current system of international law provides sufficient norms for distinction and protection of critical infrastructure and critical entities. The specific legal regime applicable to a particular conflict will depend on the circumstances of that conflict, including the parties involved, the nature of the conflict, and the relevant international and domestic laws. In many cases, there may be a need to interpret and apply these laws in a manner that is consistent with the principles of IHL and the protection of civilians and civilian objects.